2005
DOI: 10.3346/jkms.2005.20.5.732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inotropic Drugs on Mechanical Function and Oxygen Balance in Postischemic Canine Myocardium: Comparison of Dobutamine, Epinephrine, Amrinone, and Calcium Chloride

Abstract: Brief ischemic episodes that induce myocardial and coronary endothelial dysfunction may alter the responses to inotropic drugs. To determine the effects of inotropic drugs in stunned myocardium, the coronary blood flow (CBF), myocardial oxygen consumption (MVO2), and regional mechanical function in response to intracoronary dobutamine, epinephrine, amrinone, and calcium chloride (CaCl2) were measured before (normal) and 30 min after a 15-min-period occlusion of the left anterior descending artery (stunned) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Phenylephrine, adrenaline, isoproterenol and dopamine 32 can be used to ameliorate the dysfunction observed during myocardial stunning. However, some earlier investigations also found that I/R injury may dampen inotropic responses of stunned myocardium to β‐adrenoceptor stimulation 27 and the inotropic potency of dobutamine and adrenaline may be diminished in postischaemic myocardium 33 . Consistent with these reports, the present results indicate impaired physiological cellular functional responses of stunned ventricular myocytes to inotropic agents.…”
Section: Discussionsupporting
confidence: 91%
“…Phenylephrine, adrenaline, isoproterenol and dopamine 32 can be used to ameliorate the dysfunction observed during myocardial stunning. However, some earlier investigations also found that I/R injury may dampen inotropic responses of stunned myocardium to β‐adrenoceptor stimulation 27 and the inotropic potency of dobutamine and adrenaline may be diminished in postischaemic myocardium 33 . Consistent with these reports, the present results indicate impaired physiological cellular functional responses of stunned ventricular myocytes to inotropic agents.…”
Section: Discussionsupporting
confidence: 91%
“…One explanation is the lack of myocardial hypertrophy from the observed TQ-induced inotropic effect in contrast to Ns -induced cardiac effects, which include cardiac hypertrophy, positive inotropy, chronotropy, and an increased myocardial flow rate [25]. Other explanations include efficient utilization of oxygen by enhanced contractile proteins, efficient oxygen extraction, enhanced synchrony of the regional blood flow, and shortening segments [7, 34]. Further studies are required to explore and confirm the molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current available therapeutic strategies fail to prevent the progression of heart failure [6]. Furthermore, the inotropic agents used to augment cardiac contractility, including digoxin, catecholamines, and dopamine, are limited by their undesirable effects [7, 8], such as tachycardia and increased metabolic demand, which could consequently lead to cardiac ischaemia and arrhythmias [9]. Therefore, there is a growing need for new inotropes that are economical and medically safe.…”
Section: Introductionmentioning
confidence: 99%